Information, Risk Sharing and Incentives in Agency Problems - Jia Xie (Bank of Canada, 2015)
This paper studies the use of information for incentives and risk sharing in agency problems. When the principal is risk neutral or the outcome is contractible, risk sharing is unnecessary or completely taken care of by a contract on the outcome. In this case, information systems are ranked according to their informativeness of the agent's action. When the outcome is noncontractible, however, the principal has to rely on imperfect information for both incentives and risk sharing. Under the first-order approach, we characterize a problem-independent ranking of information systems, which is relaxed from Gjesdal's (1982) criterion. We also find sufficient conditions justifying the first-order approach.
Keywords: D8; 330; Economic models